2019
DOI: 10.1007/s00027-019-0633-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological fluctuations modulate phototrophic responses to nutrient fertilization in a large and shallow lake of Southwest China

Abstract: Hydrological fluctuations modulate phototrophic responses to nutrient fertilization in a large and shallow lake of Southwest China. Aquatic Sciences, 81(2), [37].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…The area belongs to the north subtropical drying monsoon and mid-tropical humid monsoon climate with distinct dry and wet seasons, with high precipitation in summer. In the region, the annual average precipitation is about 928.3 mm, the average value of annual sunshine hours is 2300 h and the average air temperature is around 18 • C [20]. The lake never freezes.…”
Section: Study Area and Data Acquisitionmentioning
confidence: 99%
See 4 more Smart Citations
“…The area belongs to the north subtropical drying monsoon and mid-tropical humid monsoon climate with distinct dry and wet seasons, with high precipitation in summer. In the region, the annual average precipitation is about 928.3 mm, the average value of annual sunshine hours is 2300 h and the average air temperature is around 18 • C [20]. The lake never freezes.…”
Section: Study Area and Data Acquisitionmentioning
confidence: 99%
“…To determine regime shifts using response variables, and to explore the potential drivers, the first step was to establish the conceptual stressor-response relationships in Lake Yilong. Previous studies showed that external nutrient loads are definitely the fundamental drivers (stressors) across the years, while other human activities (e.g., fish/aquaculture) and hydrological factors also had great effects at different periods [20,35]. With increasing loads from the watershed, the concentrations of TN and TP increased and subsequently caused a high level of algal biomass; the corresponding negative effects were high turbidity, low SD and the vanishing of submerged macrophytes.…”
Section: Determination Of Regime Shift Presencementioning
confidence: 99%
See 3 more Smart Citations